The role of strategic planning in improving the effectiveness of healthcare systems: A literature review - Nirna Dwi Anggraini; Donna Ndari Santoso Putri; Heri Iswanto (PT WIM Solusi Prima, 2026)
Healthcare services are a crucial component in improving public health, yet their effectiveness still faces various challenges, such as service quality, resource efficiency, and patient satisfaction. One approach that can be used to address these issues is strategic planning a systematic process for effectively and efficiently establishing organizational goals and strategies. This study employs a literature review method by analyzing 10 relevant scientific articles on strategic planning in healthcare. The findings indicate that strategic planning plays a crucial role in enhancing the effectiveness of healthcare services, particularly in human resource management, service quality improvement, and organizational performance. The implementation of appropriate strategies, such as SWOT analysis, human resource competency development, and the optimization of facilities and infrastructure, has proven effective in improving service quality and patient satisfaction. However, the implementation of strategic planning still faces challenges, including budget constraints, a lack of continuous training, and the uneven distribution of healthcare personnel. Additionally, the effectiveness of strategies is influenced by the comprehensiveness of performance indicators and the evaluation systems used. Therefore, there is a need to strengthen data-driven strategic planning, enhance human resource competencies, and improve facilities and infrastructure to support the effectiveness of healthcare services.